Development of Vehicle Transhipment in Sri Lanka: Case Study of Hambantota Port - Pothupitiyage, D.K.D.; Amaratunge, S.; Withanawasam, M.P.K. (University of Sri Jayewardenepura, Nugegoda., 2015)
Due to the characteristics unique to vehicle transhipment, the Colombo Port is unable to handle much vehicle transhipment, since it gives priority to container transhipment. As an effective measure to ease the long berthing delays experienced by car carriers at the Port of Colombo, Sri Lanka Port Authority has decided to route all such vessels to the Hambantota Port, which is officially known as MRMRP and is now "vigorously campaigning" to make the MRMRP a "preferred transhipment hub port for vehicles". A transhipment hub port is determined by not just one factor but a collection of factors. This study investigates the reliability of twelve such factors including location, cost, infrastructure, other services provided by port, port safety, man power, industrial zone, port connectivity, hinterland accessibility, port efficiency, government policies and international relationships to create a vehicle transhipment hub at Hambantota. Whether a port is used as a hub port or not is solely decided by shipping lines. Thus, this study includes a survey with a sample of shipping companies who are engaged in vehicle transhipment in Sri Lanka. Since vehicle transhipment activities are only being carried out at the Hambantota port, this study has been developed as a case study of the Hambantota port. SWOT Analysis tool has been used to strategically analyze each factor. The most influencing factor to create a hub port in Hambantota has been identified through the weights given by shipping companies. According to these shipping companies’ point of view, the great possibility of converting Hambantota port to a vehicle transhipment hub has been recognized and recommendations have been presented for policy makers’ consideration to take immediate action for the health of this particular industry. The location of the Hambantota Port plays a vital role and in most of the cases, the management is the prevalent weakness of the port. Opportunities in each aspect have not been correctly utilized by the port authorities yet. This study strongly recommends to the responsible parties to make provisions in order to to convert weaknesses in to strengths and to capitalize on opportunities.
Keywords: Transhipment; MRMRP; SWOT analysis